PENGARUH MACAM MULSA DAN PUPUK KANDANG TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KACANG PANJANG (Vigna Sinensis L.) - Choirul Anam; Kevin Kevin; Dian Eka Kusumawati (Agriculture faculty, Darul ‘Ulum Islamic University (UNISDA) of Lamongan, 2021)
Long beans are seasonal vegetable crops that are widely used by people in Indonesia and are one type of vegetable that is sold daily. The use of long beans is very diverse, which is served for a variety of dishes from raw to cooked. The parts of long bean plants that can be consumed are the leaves and pods. The purpose of this study was to determine how much influence the application of mulch and manure had on the growth of long beans (Vigna Sinensis L.). The study was conducted in Jatenan Village, Kedungpring District, Lamongan Regency. The altitude of the place is ± 7 meters above sea level. The time of the study was carried out from February to March 2021, using the factorial Randomized Block Design (RAK) method, which consisted of 2 factors with 3 replications. The results of the study of the Effect of Cow Manure Application on the Growth and Production of Long Beans (Vigna Sinensis L.) The results of the study of the Effect of Mulch and Cow Manure on the Growth and Production of Long Bean Plants (Vigna Sinensis L.) can be seen that the best treatment is the goat manure treatment (P1) and plastic mulch treatment (M2) than the other treatments.